T1 mapping and cardiac magnetic resonance feature tracking in mitral valve prolapse - Guglielmo, Marco; Fusini, Laura; Muscogiuri, Giuseppe; Baessato, Francesca; Loffreno, Antonella; Cavaliere, Annachiara; Rizzon, Giulia; Baggiano, Andrea; Rabbat, Mark G.; Muratori, Manuela; Tamborini, Gloria; Danza, Ludovica M. L.; et al. (European radiology, 2021)
Objectives T1 mapping (T1-map) and cardiac magnetic resonance feature tracking (CMR-FT) techniques have been introduced for the early detection of interstitial myocardial fibrosis and deformation abnormalities. We sought to demonstrate that T1-map and CMR-FT may identify the presence of subclinical myocardial structural changes in patients with mitral valve prolapse (MVP). Methods Consecutive MVP patients with moderate-to-severe mitral regurgitation and comparative matched healthy subjects were prospectively enrolled and underwent CMR-FT analysis to calculate 2D global and segmental circumferential (CS) and radial strain (RS) and T1-map to determine global and segmental native T1 (nT1) values. Results Seventy-three MVP patients (mean age, 57 ± 13 years old; male, 76%; regurgitant volume, 57 ± 21 mL) and 42 matched control subjects (mean age, 56 ± 18 years; male, 74%) were included. MVP patients showed a lower global CS (− 16.3 ± 3.4% vs. − 17.8 ± 1.9%, p = 0.020) and longer global nT1 (1124.9 ± 97.7 ms vs. 1007.4 ± 26.1 ms, p < 0.001) as compared to controls. Moreover, MVP patients showed lower RS and CS in basal (21.6 ± 12.3% vs. 27.6 ± 8.9%, p = 0.008, and − 13.0 ± 6.7% vs. − 14.9 ± 4.1%, p = 0.013) and mid-inferolateral (20.6 ± 10.7% vs. 28.4 ± 8.7%, p < 0.001, and − 12.8 ± 6.3% vs. − 16.5 ± 4.0%, p < 0.001) walls as compared to other myocardial segments. Similarly, MVP patients showed longer nT1 values in basal (1080 ± 68 ms vs. 1043 ± 43 ms, p < 0.001) and mid-inferolateral (1080 ± 77 ms vs. 1034 ± 37 ms, p < 0.001) walls as compared to other myocardial segments. Of note, nT1 values were significantly correlated with CS ( r , 0.36; p < 0.001) and RS ( r , 0.37; p < 0.001) but not with regurgitant volume. Conclusions T1-map and CMR-FT identify subclinical left ventricle tissue changes in patients with MVP. Further studies are required to correlate these subclinical tissue changes with the outcome. Key Points • T1 mapping (T1-map) and cardiac magnetic resonance feature tracking (CMR-FT) techniques have been introduced for the early detection of interstitial myocardial fibrosis and deformation abnormalities. • In MVP patients, we demonstrated a longer global nT1 with associated reduced global circumferential (CS) and radial strain (RS) as compared to control subjects. • Among MVP patients, the mid-basal left ventricle inferolateral wall showed longer nT1 with reduced CS and RS as compared to other myocardial segments. Further studies are required to correlate these subclinical tissue changes with the outcome.